Access to a chiral phosphine-NHC palladium(II) complex via the asymmetric hydrophosphination of achiral vinyl azoles - Seah, Jeffrey Wee Kiong (2022)
Enantioenriched phosphine azoles were synthesized in high yields via palladium-catalyzed asymmetric hydrophosphination with excellent yields and enantioselectivities under mild reaction conditions. One of the phosphine azoles was methylated and complexed to palladium(II) cleanly to give a chiral phosphine-NHC palladium(II) complex with excellent overall conversion.